Faktor-faktor yang mempengaruhi pemindahan latihan komputer ke tempat kerja - Matanul, Brenda F. (Universiti Malaysia Sarawak (UNIMAS), 2002)
This study was aimed to determine the perception of staff towards the transfer of computer training and thefactors that influence the transfer. This study was conducted at Human Resource Department (HRD), Sabah. A survey methodology was used in collecting the data and 43 staffs from various ranks were ~lected as samples in this study. Statistical analysis such as frequency, percentage, Kruskal-Wallis, correlation and regression analysis was used to analyze the data. This study revealed that the entire respondent (/00%) had positive perception towards the transfer of computer training. The finding also revealed that there is no significant difference among respondents of various demographic characteristics in terms of their perception towards the transfer of training. The next finding revealed that there were significant relationship between perception and selfabilities (r=0.612, p=O.OOO) and motivation (r=0.650, p=OJ)()(). while there were no significant relationship between supervisor support and workplace environment. Multiple linear regression shows that staff motivation is the most dominant factor influencing perception, contributing 42.3% to the perception of staff towards the transfer of training. This IJI«IlIS, the staff motivation need to be given a special emphasis in ensuring the transfer of computer training 10 the workplace. It is suggested that the organization should explain to the staff what is the main purpose of the training and give a useful training that can be use in their work in order to increase their motivation to transfer the training to the workplace.